Cover Journal of Infrastructure & Facility Asset Management - Hitapriya Suprayitno (Departemen Teknik Sipil, Institut Teknologi Sepuluh Nopember, 2019)
Preliminary Recognition of River Infrastructure Mahendra Andiek Maulana, Hitapriya Suprayitno & Ria Asih Aryani Soemitro Reflection on Data Error Identification Methods for Field Survey Data on Commuter Train Pasengger Travel Behavior Hitapriya Suprayitno & Ria Asih Aryani Soemitro Gradation Analysis of Reclaimed Asphalt Pavement from National Road as Asphalt Concrete Layer Ari Widayanti, Ria Asih Aryani Soemitro, Januarti Jaya EkaPutri& Hitapriya Suprayitno Mental Tasks EEG Signal Classification Using Support Vector Machine Wahyu Caesarendra, Syahara U. Lekson & Muhammad Agung Searching the Appropriate Minimum Sample Size Calculation Method for Commuter Train Passenger Travel Behavior Survey Anita Susanti, Ria Asih Aryani Soemitro, Hitapriya Suprayitno & Vita Ratnasari